The Effect of Information System Quality, Perceived Usability, and Information Quality on User Satisfaction of Finance Management System (FMS) Applications - Asih Waris Lestari; Aloysius Harry Mukti; M.F Christiningrum (Basic and Applied Accounting Research Journal, 2023)
Information technology plays an important role in financial system, company need this for quality improvement. The purpose of this study was to examine and analyze the effect of information system quality, perceived benefits, and information quality on user satisfaction at PT. Wijaya Karya (Persero) Tbk. The number of respondents used as many as 45 employees of PT. Wijaya Karya (Persero) Tbk. This research is quantitative by using the analysis method with SmartPLS3 program. The results of this study indicate that the influence of information system quality, perceived benefits, and information quality have a positive effect on application user satisfaction.